Rituximab maintenance significantly reduces early follicular lymphoma progressions in patients treated with frontline R-CHOP - Procházka, Vít; Belada, David; Janíková, Andrea; Benešová, Kateřina; Mociková, Heidi; Ďuraš, Juraj; Pirnos, Jan; Kopečková, Kateřina; Campr, Vít; Fürst, Tomáš; Pytlík, Robert; Sýkorová, Alice; et al. (EJHaem, 2020)
Twenty percent of patients with high-tumor-burden (HTB) follicular lymphoma (FL) develop progression/relapse of disease (POD) within 24 months of frontline immunochemotherapy. Unfortunately, about 50% of these patients die within 5 years since POD event. Rituximab maintenance was proven to reduce relapse rate in responding FL, but its role on preventing POD was not defined. We analyzed 1360 HTB-FL patients from the Czech Lymphoma Study Group registry treated with frontline rituximab-containing regimen. Of those, 950 cases received rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) and achieved complete or partial remission: 712 patients received rituximab maintenance (MAINT) and 238 were a historical observational cohort (OBS). We have proposed a modified POD24 (mPOD24) endpoint for the chemosensitive patients calculated from the end-of-induction (EOI). Survival rates since EOI were as follows: 5-year overall survival (OS) 86.2% versus 94.5% in the OBS and MAINT groups, respectively (P < .001) and 5-year progression-free survival 58.5% (OBS) and 75.4% (MAINT) (P < .001). The Cox proportional hazards model showed a decrease in mPOD24 incidence in the MAINT group with the overall hazard rate reduced by 56% (hazard ratio = 0.44; P < .001). The cumulative incidence of mPOD24 was reduced from 24.1% in OBS to 10.1% in MAINT (P < .001). Comparison of non-mPOD24 cases showed OS similar to that in the general population. Rituximab maintenance given after R-CHOP resulted in a 2.4-fold reduction in mPOD24 incidence. Once the non-POD24 status is achieved, FL does not shorten the patients' life expectancy.
Keywords: maintenance; follicular lymphoma; rituximab; early progression